Progress Report on Crisis Resolution. (Policy Papers; Policy Paper ;, 2005)
Describes progress in the inclusion of CACs in international sovereign bonds. Provides an update of efforts to broaden the consensus on the Principles. Reports on developments in recent sovereign debt restructuring cases. Discusses progress in the Evian Approach and other Paris Club issues. Provides a summary of the aforementioned paper on the determinants and prospects for regaining market access.